Establishing the effectiveness of life cycle assessment to assess the environmental impact of passenger cars using biofuels: A Review - Marchant, Denis; Christensen, Jesper; Davies, Huw (Universitas Muhammadiyah Surakarta, 2023)
Predictions and decisions made by legislators may be partially or wholly informed by the results of life cycle assessment studies, but the outcomes can vary significantly. This review seeks to establish whether existing life cycle assessment study results are accurate and if there are errors or deficiencies in life cycle inventory databases, chosen methodologies, or choice of life cycle assessment tool that may impact the outcome of life cycle assessment studies. The context of the work is set against the role bioethanol/gasoline blends might play in reducing the environmental impact of internal combustion engine-powered vehicles. The findings indicate inaccuracies exist and that there are various reasons for this. The accuracy of life cycle assessment results is affected by differences and inconsistencies that occur between life cycle inventory databases, the choice of life cycle inventory databases and life cycle assessment tools and because, in many cases, life cycle assessment methodology does not specify whether the biofuel content in the fuel is considered. The increase in the average age of biofuel-compatible passenger cars challenges the validity of results obtained by employing the commonly used approach based on fixed annual mileage profiles and lifetime activity. Uncertainty is a significant factor, and more attention should be paid to uncertainty analysis. Evidence shows the use of biofuels can deliver considerable environmental gains and reductions in CO2, especially in blends containing a higher percentage of biofuel.